Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement. Issue 3 (18th March 2019) - Nisbet, E. G.; Manning, M. R.; Dlugokencky, E. J.; Fisher, R. E.; Lowry, D.; Michel, S. E.; Myhre, C. Lund; Platt, S. M.; Allen, G.; Bousquet, P.; Brownlow, R.; Cain, M.; et al.
Abstract: Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1, 775 ppb in 2006 to 1, 850 ppb in 2017. Simultaneously the 13 C/ 12 C isotopic ratio (expressed as δ 13 CCH4 ) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained. Plain Language Summary: The rise in atmospheric methane (CH4 ), which began in 2007, accelerated in the past 4 years. The growth has been worldwide, especially in the tropics and northern midlatitudes. With the rise has come a shift in the carbon isotope ratio of the methane. The causes of the rise are not fully understood, and may include increased emissions and perhaps a decline in the destruction of methane in the air. Methane's increase since 2007 was not expected in future greenhouse gas scenarios compliant with the targets of the Paris Agreement, and if the increase continues at the same rates it may become very difficult to meet the Paris goals. There is now urgent need to reduce methane emissions, especially from the fossil fuel industry. Key Points: Atmospheric methane is rising; its carbon isotopic ratio has become more depleted in C‐13 The possible causes of the change include an increase in emissions, with changing relative proportions of source inputs, or a decline in methane destruction, or both If this rise continues, there are significant consequences for the UN Paris Agreement